THE PROPERTY IN ISLAM (IMAM MUHAMMAD ABU ZAHRAH’S PERSPECTIVE) - BADRUN SYAHIR; MUSTAFFA ABDULLAH (Islamiconomic: Jurnal Ekonomi Islam, 2017)
Based on an observation through many communities, it is obviously that people are very careless on the possession of property, or even merely to get the advantage from it. They used not to think about, but prefer to neglect, the rightness of owning, the rightness of acquiring and the rightness of spending the property. In their mind is whatever they can gain, irrespective to the ethic and moral on the way of reaching and gaining, is totally belong to them, and they are free to do so ever. It is a very liberal concept of property.